A Theory of Non-Coasean Labor Markets - Andrés Blanco; Andres Drenik; Christian Moser; Emilio Zaratiegui (Institute of Labor Economics (IZA), 2023)
We develop a theory of labor markets in a monetary economy with four realistic features: search frictions, worker productivity shocks, wage rigidity, and two-sided lack of commitment. Due to the non-Coasean nature of labor contracts, inefficient job separations occur in the form of endogenous quits and layoffs that are unilaterally initiated whenever a worker's wage-to-productivity ratio moves outside an inaction region. We derive sufficient statistics for the aggregate labor market response to a monetary shock based on the distribution of workers' wage-to-productivity ratios. These statistics crucially depend on the incidence of inefficient job separations, which we show how to identify using readily available microdata on wage changes and worker flows between jobs.
Keywords: E12; E31; D31; 330; inflation; monetary policy; wage rigidity; wage inequality; unemployment; inefficient job separations; quits; layoffs; directed search; commitment; stopping times; continuous-time methods; variational inequalities